Smart card attendance systems in educational institutes: A systematic review - Muslim, Aini Khalida; Ahmad, Naveed; Mohd Dzulkifli, Dzunnur Zaily; Govinda Raj, Vimala; Ishak, Muhamad Izaidi (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Accurate attendance tracking is critical in boosting performance, regulating operational expenses, and improving accuracy of payments in different organizations. Using Radio Frequency Identification (RFID) or Near Field Communication (NFC) technology, smart card attendance has become a popular attendance mechanism that is faster and more reliable and secure, compared to its predecessors through manual and biometric. Although earlier research points to positive side effects of offloading administrative tasks, the evidence is also inconsistent and fragmented, and most researchers report on positive effects in studies of specific industries. To fill this gap, the current study proposes a productive systematic literature review (SLR) of the existing empirical studies conducted between the years 2000 and 2025 to support the effects of the implementation of smart card attendance systems on punctuality, administrative cost, and payroll accuracy. According to PRISMA 2020, literature was retrieved using Scopus, Web of Science, IEEE Xplore and ProQuest. The review would have a purpose of synthesizing the evidence in education, corporate, and in service industries so that they can come up with a consolidated evidence base. The uniqueness of the study consists in the combined analysis of the level of operational and financial success, not only providing new theoretical knowledge on the adoption of technology but also helping decision-makers in the process. The results will shape policy, minimize the number of people and improve accountability in the attendance monitoring devices.